Performance of hardboard made from mechanical pulp of tropical bamboo culms (Gigantochloa scortechinii) - Salim, Sabiha; Ashaari, Zaidon; Halis, Rasmina; Mohd Yusoff, Mohd Nor (2005)
A study on the utilization of Gigantochloa scortechinii (Buluh semantan) culms for the production of wet-process hardboard was conducted. This paper reports on i. the properties of G. scortechinii fibres after treated with sodium hydroxide (NaOH) or steamed prior to pulping using refiner mechanical pulping (RMP) and, ii. the effects of pre-treatment of bamboo fibers on the hardboard mechanical and physical properties. Longer and high yield recovery of fibres was noted for NaOH pre-treated chips. Both treatments affected the fibre morphology and its colour. A total of thirty 3-mm thick hardboard (density, 900 kgm-3) were manufactured with phenol formaldehyde (PF) resin (1-2%), wax (1-2%), and alum (0.25%) added selectively during the manufacturing of the boards. All mechanical and physical properties of boards were tested in accordance with Japanese Industrial Standard for Fibreboard (JIS-A-5905, 2003). Commercial hardboard of same thickness was used for comparison purposes. Results showed that when the levels of PF resin and wax increased in the boards, the Modulus of Rupture (MOR) increases. Boards made from NaOH-treated fibers had the highest MOR values but the thickness swelling was also increased. The Internal bond (IB) for boards with 2% PF resin and 2% wax was higher than the IB of the commercial boards. As a whole the mechanical properties of the bamboo hardboards exceeded the minimum standard requirement and were more superior than the commercial hardboard made from rubberwood. However, the dimensional stability of bamboo hardboard was significantly lower than the commercial board.